The Role of Entrepreneurial Marketing to Increase Sales Products : A Phenomenological Approach of College Students’ Start Up Businesses - Iwan Sukoco; Diana Prihadini; H. Bambang Hermanto; Pratami Wulan Tresna (Technium Social Sciences Journal, 2021)
Students are no stranger to entrepreneurial activities in the campus environment. Economically, students are helped by entrepreneurship in fulfilling their daily needs while studying. The rise of students who are entrepreneurs from an early age is helped by technological advances that make young people more enthusiastic in fostering entrepreneurial spirits. However, there are not a few student start-ups that don’t continue. One of the problems lies in the marketing strategy. There are still many students who do not yet fully understand what is called Entrepreneurial Marketing, so they still use the old ways of promoting and marketing their products. The purpose of this study is to answer the question of what problems in marketing are encountered by start-up students, and what are the efforts made so that Entrepreneurial Marketing can be applied in start-ups managed by students so as to increase product sales. This is a qualitative research with a phenomenological approach. Data collection was carried out by in-depth interviews with 20 start-up students in the Jakarta, Bogor, Depok, Tangerang and Bekasi areas. This study proves that the 7 dimensions of Entrepreneurial Marketing, namely product innovation, focus on customers, focus on opportunities, be pro-active, create value creation, dare to take risks and increase human resource capacity are needed in increasing product sales.